Occurrence, distribution and viability of Anisakis spp. larvae in various kind of marketed herring products in Italy. (July 2019) - Guardone, L.; Nucera, D.; Rosellini, N.; Tinacci, L.; Acutis, P.L.; Guidi, A.; Armani, A.
Abstract: Herring is the third most commercialized fish species in the EU and a common host of Anisakis spp. larvae. The aim of this study was to assess the occurrence, distribution and viability of Anisakis spp. larvae in different kind of ready to eat (RTE) herring products. One hundred and thirty-five products, consisting of 50 smoked whole specimens and 85 filleted products were collected in Italy from 2016 to 2018. Viscera and muscle of whole herrings were visually inspected and separately submitted to artificial digestion. Filleted products were also visually inspected and digested. Natural and UV light were used for examining the residual material. Nematodes larvae viability was assessed, then they were counted, collected and identified to genus level by optical microscopy. In addition, the cox2 gene was targeted for the identification of part of the larvae. Anisakis spp. larvae were found in 56 products (41.5%) and overall 1715 larvae were collected (range 0–172 larvae/product). Most of the larvae (1559, 91%) were found in the viscera of 49 of the 50 whole herrings (98%). A statistically significant difference (p < 0.001) was observed in the positivity rate and the larval density of the remaining 156 larvae found at muscle level, as 149 larvae were found in the muscle of 31 whole herrings (positivity rate 62%, 0.022 larval density/g), while only 7 larvae were found in the 85 filleted products (positivity rate 7%, 0.001 larval density/g). Larvae were molecularly identified as A. simplex . Although all the larvae were dead, the high level of contamination of whole herrings on the market poses some issues related to the presence of a potentially hazardous defect. In particular, the significant difference between infection levels of muscle tissue of whole and filleted herrings, likely due to differences in the production process, results in a different risk of exposure to parasitic antigens. Therefore, a better management of the herring supply chain is required to improve the whole quality and to protect consumers' health. Highlights: Different kinds of herring ready to eat products were analysed by digestion. 41.5% of the products were positive for at least one visible Anisakis spp. larva. A total of 1715 dead larvae were collected. Whole smoked products were heavily contaminated at visceral and muscle level. The product category influenced the positivity rate and larval density.